A Perception of Corporate Social Responsibility in the New Era of Globalization: An Overview (International Journal of Food and Nutritional Sciences, 2022)
In the contemporary landscape of global business, the concept of Corporate Social Responsibility (CSR) has garnered increased attention. This abstract provides an overview of the evolving perception of CSR in the context of the new era of globalization. As businesses navigate the complexities of an interconnected world, the understanding of CSR has expanded beyond mere philanthropy to encompass a broader commitment to ethical practices, environmental sustainability, and social impact.This overview explores the key dimensions of CSR, examining its significance and implications within the dynamic framework of globalization. It delves into the evolving expectations of stakeholders, including consumers, investors, and communities, and how organizations are adapting their strategies to align with these shifting paradigms.The abstract further investigates the challenges and opportunities presented by the intersection of CSR and globalization. It highlights the role of businesses in contributing to sustainable development goals, fostering inclusivity, and addressing pressing global issues. By synthesizing current literature and insights, this abstract aims to contribute to a nuanced understanding of CSR in the contemporary globalized era, shedding light on the multifaceted responsibilities that corporations bear in shaping a sustainable and socially conscious future.